Contribution of Market Access Services on the Entrepreneurial Capacity of Businesswomen in Kenya - Lillian Lwayah; Kennedy Mutundu; Serah Kimaru Muchai (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study examined the effect of market access services on women entrepreneurial capabilities in Mbeere South Sub County of Embu County, Kenya. It addressed three key determinants: the development of market infrastructure, enterprise linkages, and digital inclusion. It adopted a mixed method approach utilizing convergent parallel design. Quantitative and qualitative data were gathered from the 244 women micro-entrepreneurs through semi-structured questionnaires, key informant interviews, and focus group discussions (FGDs). The study applied multiple regression to determine the effect of market access services on entrepreneurial capacity. The findings showed a strong positive relationship where market access services impact entrepreneurial capacity to a very large degree, with an R-square value of 0.876, indicating that the three predictors explained 87.6% of the variation in entrepreneurial capacity. Also, reinforcing the positive effect was the impact of each individual predictor with their coefficients being 0.335, 0.320 and, 0.291, respectively. The findings highlight the importance of initiatives that target the development of market infrastructure, the strengthening of enterprise linkages, and the promotion of digital inclusion. These measures enhance the competitiveness, productivity, and sustainability of women-owned businesses and, consequently, poverty reduction and socio-economic development improvements in rural areas. This study serves as a reference point for policymakers and a foundation for future investigations concerning women entrepreneurship in rural Kenya.